Architectural rehabilitation and conservation processes informed by augmented reality - Jones, P. (2018)
The goal of the presented research is to explore human-machine interaction and to study how Augmented Reality (AR) may be a potential tool to inform Architectural Rehabilitation and Conservation processes. Nowadays obtaining data to inform both architecture projects and real estate investments is a very bureaucratic process. City councils technicians suffers from the same difficulties when are in fieldwork to do inspections and lack a complete sort of information. This proposal considers that the use of mobile technologies as smart phones and tablets can empower these technicians to obtain building related data. The specific goal of the study aims to develop a data model and an interface that can be made available to professionals which allows an efficiently reply to the user’s needs as the system enables the gathering of updated information considering a particular building.